Novel TEA Algorithm for IP Telephony System - Samah Osama M Kamel (International Journal of Informatics and Communication Technology (IJ-ICT), 2012)
IP telephony that transmit voice calls over an IP network such as the Internet, IP telephony are growing very fast replace the traditional circuit switched infrastructure for telephony services. So we must protect all data that are transmitted from all attacks. To implement this process, the voice is encrypted, authenticated and decrypted to get the original data. The paper examines and evaluates the six encryption algorithm to minimize delay time to achieve minimum encryption time. A Novel TEA encryption Algorithm is examined for the minimum processing time to be suitable for IP Telephony which takes minimum timeDOI: http://dx.doi.org/10.11591/ij-ict.v1i1.485